PENERAPAN KONSEP DIVERSI BAGI ANAK PENYANDANG DISABILITAS PELAKU TINDAK PIDANA KEKERASAN - Siti Komariah; Kayus Kayowuan Lewoleba (Magister Hukum Universitas Semarang, 2021)
This study aims to analyze the legal protection of children with disabilities who are in conflict with the law according to the laws and regulations in Indonesia and the application of the concept of diversion for children with disabilities who are perpetrators of violent crimes. This research is motivated by the lack of research on the application of diversion to children with disabilities. The novelty of this research is that there is no research that discusses the application of diversion for children with disabilities who are in conflict with the law as perpetrators of violent crimes. The research method used is juridical-normative with a statute approach and a conceptual approach. The results of the study conclude that first, for the purpose of examining the legal process, children with disabilities are entitled to assistance from the family or companion concerned. Second, the concept of diversion can be applied to cases of violence perpetrated by children with disabilities starting from the stage of imvestigation, prosecution, to the judicial process in the District Court.